Corrosion Behavior of Al0.1CoCrFeNi High Entropy Alloy in Various Chloride-Containing Solutions - Wang, K.; Lan, A. D.; Qiao, J. W. (Frontiers in Materials, 2021)
The present work investigates the corrosion behavior of Al0.1CoCrFeNi high entropy alloy (HEA) in various concentration of chloride-containing solutions. Electrochemical tests exhibit overall excellent corrosion resistance of this alloy against the attack of Cl--containing solutions. The main type of corrosion topography presents an inter-granular feature. In addition, electrochemical impedance spectroscopy (EIS) study of immersion test of the HEA samples suggests chloride anion containing environment leads to the decline of passivation film quality. Further analysis of XPS results reveals that significant amount of elements exists with atomic state in the passive film.